Pengaruh Inovasi Produk, Tenaga Kerja, dan Pemasaran terhadap Perkembangan UMKM Kerajinan di Kecamatan Purwanegara Banjarnegara (Business and Accounting Education Journal, 2022)
This study aims to examine the effect of product innovation, labor, and marketing on the development of handicraft SMEs in Purwanegara District, Banjarnegara Regency. This quantitative study has a population of small and medium enterprises in handicrafts in Purwanegara District, Banjarnegara Regency, amounting to 75 entrepreneurs with a sample of 45 entrepreneurs. Data were collected by questionnaire and analyzed by descriptive analysis and multiple regression. The results of the study show that there is a positive influence of product innovation, labor, and marketing together on the development of handicraft SMEs. Product and labor innovation have a positive effect on the development of handicraft SMEs, while marketing does not have a positive effect on the development of handicraft SMEs.